2000
DOI: 10.1002/(sici)1098-1136(20000101)29:1<58::aid-glia6>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids inhibit LPS‐inducible cytokine mRNA expression in rat microglial cells

Abstract: The effect of cannabinoids on the induction of cytokine mRNA by rat microglial cells was examined. Exposure of neonatal rat cortical microglial cells to the exogenous cannabinoid delta(9)-tetrahydrocannabinol (THC) resulted in reduced amounts of lipopolysaccharide (LPS)-induced mRNAs for IL-1alpha, IL-1beta, IL-6, and TNF-alpha. Of these cytokine mRNAs, the response of that for IL-6 was exquisitely sensitive to THC. Similarly, exposure of microglial cells to the putative endogenous cannabinoid anandamide befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 6 publications
7
39
0
Order By: Relevance
“…In addition, THC has been shown to interfere with macrophage cell contact-dependent lysis of tumor cells, herpesvirus-infected cells, and amebae, and to deplete soluble tumoricidal activity elicited by macrophages exposed in vivo to the drug (Burnette-Curley et al 1993;Burnette-Curley and Cabral 1995). These observations are consistent with reports that THC inhibits the synthesis of proteins associated with primed and activated macrophages (Cabral and Mishkin 1989), alters cytokine secretion by activated macrophages (Watzl et al 1991;Nakano et al 1992), and inhibits cytokine gene expression by microglia (Puffenbarger et al 2000) (Fig. 3) …”
Section: Modulation Of Antigen-presenting Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, THC has been shown to interfere with macrophage cell contact-dependent lysis of tumor cells, herpesvirus-infected cells, and amebae, and to deplete soluble tumoricidal activity elicited by macrophages exposed in vivo to the drug (Burnette-Curley et al 1993;Burnette-Curley and Cabral 1995). These observations are consistent with reports that THC inhibits the synthesis of proteins associated with primed and activated macrophages (Cabral and Mishkin 1989), alters cytokine secretion by activated macrophages (Watzl et al 1991;Nakano et al 1992), and inhibits cytokine gene expression by microglia (Puffenbarger et al 2000) (Fig. 3) …”
Section: Modulation Of Antigen-presenting Cellssupporting
confidence: 89%
“…3. The potent synthetic cannabinoid agonist CP55940 inhibits proinflammatory cytokine gene expression by microglia (Puffenbarger et al 2000). Purified neonatal rat brain cortical microglia (10 6 cells) were treated with vehicle (0.01% ethanol) or CP55940 for 1 h followed by exposure to LPS (10 ng/ml) for 6 h. Total RNA was then isolated from cultures and LPSinducible cytokine mRNA species were detected using the RiboQuanti rCK-1 template set RNase protection assay (PharMingen, San Diego, CA) according to the manufacturer's instructions.…”
Section: Il-1αmentioning
confidence: 99%
“…In the course of studying this question, four observations were made: (1) the inhibitory effect of WIN55,212-2 on HIV-1 expression is not unique, in that CP55,940 also suppressed viral expression; (2) CB 2 receptors are involved in WIN55,212-2 inhibitory effect, as witnessed by significant blockade with the CB 2 receptor-selective antagonist SR144528 and the similar inhibitory effect of JWH 0-15, which has been shown to inhibit microglia activation (Ehrhart et al 2005), suggesting that suppressed microglial activation and decreased HIV-1 replication may be related; (3) downregulation of CCR5 receptors appeared to be one mechanism whereby WIN55,212-2 inhibits HIV expression, and (4) the involvement of CB 1 in this process cannot be adequately assessed because of the surprising inhibitory effect of the CB 1 receptor-selective antagonists SR141716A and AM-251. This paradoxical agonist activity of SR141716A has been previously identified in other macrophage/microglia models (Gross et al 2000;Puffenbarger et al 2000), including a report in which SR141716A's inhibitory effect on multiplication of intracellular Brucella suis in human monocytes prompted the authors to suggest that this cannabinoid be considered for treatment of infections caused by intracellular gram-negative bacteria (Gross et al 2000). The observation in the present study that agents such as WIN55,212-2, CP55,940, and SR141716A (which has also been shown to be effective in the treatment of obesity (Despres et al 2005) and is about to be marketed under the trade name Rimonabant®), have the capacity to inhibit HIV-1 expression should foster further exploration of cannabinoids as potential antiviral agents.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, cannabinoids inhibit lipopolysaccharide-induced cytokine expression in cultured rat microglia [51,52,96]. It is therefore likely that both synthetic and endogenous cannabinoids block the activation of microglia, but this effect appears to be independent of the CB1 receptor because the CB1 receptor-selective antagonists SR141716A and AM251 are unable to reverse the inhibition of microglia activation by CB1 agonists [52,96].…”
Section: Neuroprotection Via the Cb1 Receptormentioning
confidence: 99%
“…However, recent data support the expression of CB2 receptors in microglial cells [98], astrocytes and even some neuron subpopulations [97]. It has been shown that CB2 receptors affect the migration [98] and production of cytokines [96] and nitric oxide (NO) [99] by microglial cell cultures in vitro. Another recent study showed that activation of CB2 receptors prevents neurotoxicity by inhibiting beta-amyloid peptide activation of microglia [72], although the CB2 receptor-selective antagonist SR144528 was unable to reverse the ability of cannabinoids to inhibit lipopolysaccharide-induced cytokine mRNA expression in cultured microglia [52,96].…”
Section: Neuroprotection Via the Cb1 Receptormentioning
confidence: 99%